2018
DOI: 10.12659/ajcr.910166
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Wiring of a Recanalized Thrombotic Lesion in the Right Coronary Artery Analyzed with Optical Coherence Tomography

Abstract: Patient: Male, 87Final Diagnosis: Recanalized thrombotic lesionSymptoms: Chest painMedication: —Clinical Procedure: GoodSpecialty: CardiologyObjective:Rare diseaseBackground:Recanalized thrombi are usually unrecognized in conventional coronary angiography. However, multiple channels have been observed in recanalized thrombotic lesions. Therefore, the wire apparently crosses the lesion in some difficult cases. We analyzed the cause of difficult wiring of a recanalized thrombotic lesion using optical coherence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…SRCT were identified, in our study, as culprit or non-culprit lesions for ACS patients. Data from the literature show that the 62 SRCT lesions may be asymptomatic -20 cases (10-12, 20, 22, 26, 28) or symptomatic, associated with stable CAD -23 cases (2,10,13,17,20,21,24,25,(29)(30)(31)(32), UA -5 cases (2,18,27) or acute STEMI -12 cases (2,10,14-16). Other two cases had an undeclared clinical condition (3,23).…”
Section: Fourth Spontaneous Recanalization Of Coronary Thrombus (Srctmentioning
confidence: 99%
See 1 more Smart Citation
“…SRCT were identified, in our study, as culprit or non-culprit lesions for ACS patients. Data from the literature show that the 62 SRCT lesions may be asymptomatic -20 cases (10-12, 20, 22, 26, 28) or symptomatic, associated with stable CAD -23 cases (2,10,13,17,20,21,24,25,(29)(30)(31)(32), UA -5 cases (2,18,27) or acute STEMI -12 cases (2,10,14-16). Other two cases had an undeclared clinical condition (3,23).…”
Section: Fourth Spontaneous Recanalization Of Coronary Thrombus (Srctmentioning
confidence: 99%
“…OCT was the only SRCT imaging method for our study, as it was for 56 of the 62 cases reported in the literature (2, 10-12, 14-23, [26][27][28][29]31). IVUS was used in 3 cases (3,24,25), while both OCT and IVUS were used in other 3 cases (13,30,31).…”
Section: Fourth Spontaneous Recanalization Of Coronary Thrombus (Srctmentioning
confidence: 99%
“…Therefore, we need to improve primary prevention strategies and treatment of cardiovascular disease to reduce worldwide mortality from this disease [5]. The development of devices (guidewires and MCs) and the advance of techniques such as retrograde approach contributed to the improvement in success rates and long-term outcomes for CTO patients [1][2][3]. Even if a guidewire passes retrogradely like in this case, the establishment of the retrograde system may be difficult in some cases since the MC cannot pass retrogradely.…”
Section: Discussionmentioning
confidence: 99%
“…Guidewires and microcatheters (MCs) have developed remarkably over recent years. Furthermore, the advance of techniques such as retrograde approach has contributed to the improvement of success rates for the interventional treatment of chronic total occlusion (CTO) [1][2][3]. In cases of a long CTO with severe tortuosity or second attempt, there is a high possibility that the retrograde approach will be required.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been several advances in treatment modalities. In instances where lesions prevent wires from passing through, double-lumen catheter and parallel wire techniques have been useful for entering adjacent cavities [9]. In addition, scoring and cutting balloons might be effective for penetrating partition walls.…”
Section: Discussionmentioning
confidence: 99%